Association of C- peptide Levels and Type 1 Diabetes in Urban and Rural areas of South India - Sujata M Jali; Mallikarjun V Jali; Sridhar Gagagane; Jyoti Wasedar; Prachi Patil (RGUHS Journal of Medical Sciences)
Background Type 1 diabetes T1D presents as a severe chronic disorder affecting 5-10 of diabetes cases typically emerging earlier in life compared to type 2 diabetes T2D. Despite advancements the global incidence of T1D continues to rise posing significant short-term and long-term implications. Characterised by the destruction of pancreatic beta cells T1D results in absolute insulin deficiency with most cases attributed to autoimmune-mediated loss of beta cells type 1a and a minority stemming from idiopathic beta cell destruction or failure type 1b. Although traditionally perceived as predominant in children and adolescents T2D diagnoses in youth are increasingly prevalent.Methods This prospective study was conducted on thirty-one individuals diagnosed with T1D and seeking treatment at the KLES Diabetes Centre Belagavi Karnataka India. A single fasting blood sample approximately 10 mL was collected from each participant via peripheral venipuncture. According to the manufacturers instructions serum C-peptide levels were measured in all samples using a validated Chemiluminescent Immuno-Assay CLIA kit.Results The mean C-peptide levels were significantly higher 1.12 ngmL in participants with disease onset between 11 and 15 years than in those with onset between 0 and 5 years 0.57 ngmL. The participants had a mean disease duration of 6.93 years ranging from 3 to 15 years with 14 45.1 having a disease duration of 0-5 years 7 22.8 with 6ndash10 years and 10 32.2 with 11ndash15 years of type 1 diabetes.Conclusion This study investigated the relationship between C-peptide levels disease duration and age at onset in individuals with Type 1 Diabetes T1D. Our findings suggest a potential link between later diseaseonset 10-15 years and higher C-peptide levels which might indicate a slower disease progression in older individuals diagnosed with T1D.nbsp However a longer disease duration was positively correlated with a gradual decline in C-peptide levels.